FORMATION OF THE EMPIRICAL COMPONENT SPIRITUALITY OF FUTURE TEACHERS BY MEANS TRAINING TASKS - N.V. Dolgaya (Academy of Cognitive and Natural Sciences, 2007)
In this article author examines system of training's tasks which favour the forming of empirical component of future teacher's spirituality.